Composite coal slag for sewage treatment and preparation method thereof

By adsorbing the photothermal converter on the sintered cinder block to form composite cinder, the complex and cost-effective preparation of existing photothermal conversion materials is solved, and efficient photothermal conversion and water evaporation effects are achieved, which is suitable for industrial applications.

CN118685151BActive Publication Date: 2025-03-18CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410699723.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-03-18
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

In the existing solar-driven interface evaporation technology, the preparation method of photothermal conversion materials is complex, relies on precious metal elements, and the production raw materials are expensive and are not suitable for industrial production and use.

Method used

Compound cinders are used as the substrate for photothermal conversion materials, and composite cinders with high visible light absorption efficiency are formed by sintering the burned cinder solid waste into cinder blocks and adsorbing a photothermal converter such as polypyrrole, carbon black or graphite on its surface.

Benefits of technology

It realizes a simplified preparation process, reduces material costs, improves photothermal conversion efficiency and water evaporation rate, and is suitable for industrial production and wastewater treatment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685151B_ABST
    Figure CN118685151B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sewage treatment, and in particular to a composite coal slag for sewage treatment and a preparation method thereof, wherein the preparation method includes the following steps: Step 1: collect and compress the burned coal slag solid waste and sinter it into a coal slag block; Step 2: immerse the coal slag block in a photothermal conversion agent solution, and dry and solidify it into a composite coal slag after adsorption. By controlling the density, porosity and adsorbed photothermal conversion amount of the composite coal slag, it can be ensured that the composite coal slag can be used for general industrial sewage treatment, and the problem of coal slag solid waste recycling is solved, which has practical industrial utilization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and in particular relates to a composite coal slag for sewage treatment and a preparation method thereof. Background Art

[0002] Solar-driven interfacial evaporation technology is a very promising low-energy sewage treatment and freshwater production technology developed in recent years. This technology converts light energy into heat energy, heats water molecules at the interface to produce steam, and produces fresh water after condensation. Solar-driven interfacial evaporation technology can produce clean fresh water from seawater, salt water or sewage. It has the advantages of energy saving, environmental protection, low cost and scalability, and has broad application prospects.

[0003] At present, solar-driven interfacial evaporation technology relies on photothermal conversion materials. For example, a Chinese patent with publication number CN117487527A in the prior art provides a solar water evaporation photothermal conversion material, its preparation method and application. The photothermal conversion material is composed of a composite of flower-shaped MoS2 and a porous carbon film. The flower-shaped MoS2 is composed of mutually crossed nanosheets. The photothermal conversion material is prepared by a phase transformation method and a hydrothermal method. The synergistic absorption and conversion capabilities of the porous carbon film and the flower-shaped MoS2 for sunlight effectively improve the efficiency of solar water evaporation. The structure is optimized to improve the surface undulation, and it has good refraction and absorption of light, which effectively reduces the reflection of light on the membrane surface and improves the efficiency of solar water evaporation.

[0004] Another example is a Chinese patent with publication number CN117073240A in the prior art, which provides a method for preparing a photothermal conversion assembly and its application, wherein the metal salt is mixed evenly with MAX ceramic powder, calcined in an inert gas atmosphere, cooled naturally, and washed with deionized water to obtain a MXene-loaded metal nano / micron particle material; the above-prepared material is stirred and mixed evenly with a PTFE emulsion, applied to the surface of the sponge with a brush, and dried naturally to obtain a photothermal conversion assembly. The photothermal conversion assembly of the present invention synergistically utilizes the good sunlight absorption capacity of the MXene material and the plasmon effect of in-situ generated metal nano / micron particles to efficiently convert solar energy into interfacial thermal energy. The prepared photothermal conversion assembly has a self-floating characteristic and can generate an ultra-high interfacial evaporation temperature at the solution interface. The prepared photothermal conversion assembly has excellent performance in seawater desalination, brine desalination, and photothermal activation of persulfate to degrade organic pollutants.

[0005] The preparation method of the photothermal conversion material in the above-mentioned prior art is complicated, relying on complex micro-nanotechnology and precious metal elements, and the cost of producing raw materials is high, which is not suitable for industrial production and use. Summary of the invention

[0006] The main purpose of the present invention is to provide a composite coal slag for sewage treatment and a preparation method thereof, wherein the coal slag solid waste is treated and then combined with a photothermal conversion agent to prepare a photothermal conversion material that can be used for solar-driven interface evaporation technology, thereby solving the post-treatment problem of coal slag solid waste and the additional energy consumption and cost problems caused by sewage treatment such as coal washing, and can be used for sewage treatment and seawater desalination. In addition, the preparation method of the present invention is simple, the material cost is low, and it is more suitable for practical application, and has industrial utilization value.

[0007] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions:

[0008] First, the present invention provides a method for preparing composite coal ash for sewage treatment, comprising the following steps:

[0009] Step 1: Collect and compress the burned coal slag solid waste into coal slag blocks;

[0010] Step 2: Immerse the coal slag block in the photothermal conversion agent solution, and dry and solidify it into composite coal slag after adsorption is completed.

[0011] Furthermore, in the step 1, the sintering temperature is 300-400° C. and the sintering time is 2-3 hours.

[0012] Furthermore, the porosity of the cinder block in step 1 is 70-90%; the density is 0.7-0.9 g / cm 3 .

[0013] Furthermore, the photothermal conversion agent in step 2 includes any one of polypyrrole, carbon black and graphite.

[0014] Furthermore, in step 2, the concentration of the photothermal conversion agent solution is 20-30 g / ml, and the adsorption time is 0.5-1 h.

[0015] Beneficial effects of the present invention:

[0016] 1) In the present invention, when the coal cinder block is sintered, gas exhaust will be generated, and the space occupied by the original elements will become holes. At the same time, a large amount of carbon dioxide and hydrogen sulfide and other gases generated by combustion will escape from the coal block. These gases pass through the coal cinder to form certain gas channels, so that the coal cinder has a loose and porous physical structure. The size of these pores is generally from hundreds of nanometers to tens of microns. This porous structure with different morphology and size is conducive to increasing the specific surface area of ​​the coal cinder block and improving its water adsorption performance. At the same time, these tiny air islands can provide capillary force so that the coal cinder can better adsorb water molecules, improving its application effect in pumping water and other aspects.

[0017] At the same time, the surface of coal slag is rich in some hydrophilic chemical groups, such as hydroxyl groups, which can enhance the interaction between it and water molecules, further enhancing the adsorption capacity, adsorption efficiency and adsorption effect of coal slag. Therefore, through the coordinated regulation of physical adsorption and chemical adsorption, the water adsorption capacity of composite coal slag is greatly enhanced, which has a positive effect on the water supply capacity of subsequent interfacial photothermal water evaporation.

[0018] 2) In the present invention, the photothermal conversion agent is compounded on the coal slag solid waste to expand the wavelength range of the absorption spectrum of the coal slag, greatly enhancing the material's ability to absorb sunlight, and the sunlight absorption rate from visible light to near-infrared band is increased from 70% to more than 96%. In this way, the utilization and absorption of sunlight is converted into thermal energy, thereby enhancing the interface photothermal conversion efficiency.

[0019] When the solar energy absorbed by the composite coal slag is converted into heat, it can be used to improve the heat conversion efficiency of the system. This heat is localized in a thin layer of water on the surface of the water body, and will not diffuse into the water body to cause additional energy loss. Therefore, it is used to achieve efficient light-to-heat conversion efficiency during processes such as interfacial water evaporation. Combined with the strong water adsorption capacity of the composite coal slag itself, it can work synergistically during interfacial water evaporation, accelerate the water evaporation rate, and improve the processing efficiency.

[0020] 3) The present invention uses coal slag produced during coal combustion or coal gasification as the main base material, and reprocesses the coal slag to produce composite coal slag with high visible light absorption efficiency, which can not only meet the requirements for industrial wastewater treatment generated by coal washing, but also solve the problem of coal slag solid waste treatment, provide a new channel for coal slag solid waste treatment, save a lot of costs, and have strong practical application value. At the same time, the method for preparing composite coal slag of the present invention is simple, and it can be used after only high-temperature sintering and adsorption of photothermal conversion agent, and the production cost is very low, which is suitable for industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the visible light-near infrared absorption curve of the cinder block without adding photothermal conversion agent;

[0022] Figure 2 This is a visible light-near infrared absorption curve of the composite coal slag in Example 1 of the present invention;

[0023] Figure 3 This is a real picture of the cinder block sample without adding photothermal conversion agent;

[0024] Figure 4 This is a physical picture of the sample of composite coal slag in Example 1 of the present invention;

[0025] Figure 5 This is a graph of water evaporation rate during the process of treating industrial wastewater with composite coal ash under sunlight in Example 1 of the present invention.

[0026] Figure 6 This is a diagram of the seawater desalination operation of the composite coal slag under a xenon lamp in a laboratory in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] Example 1

[0028] This embodiment provides a composite coal slag for sewage treatment, wherein the composite coal slag is adsorbed with a photothermal conversion agent, and the adsorption mass of the photothermal conversion agent is 4% of the weight of the composite coal slag. The density of the composite coal slag is 0.8g / cm 3 , the porosity is 90%.

[0029] This embodiment also provides a method for preparing composite coal slag for sewage treatment, which is used to prepare the composite coal slag for sewage treatment, and specifically comprises the following steps:

[0030] Step 1: Collect and compress the burned coal slag solid waste into coal slag blocks;

[0031] Specifically, the coal slag solid waste discharged from coal burning in industrial production such as thermal power plants, industrial and civil boilers and other equipment is collected and pressed into shape. The formed coal slag solid waste is placed in a combustion furnace and heated and burned into coal slag blocks at a combustion temperature of 350°C and a combustion time of 2.5 hours.

[0032] Step 2: Immerse the coal slag block in the photothermal conversion agent solution, and dry and solidify it into composite coal slag after adsorption is completed.

[0033] Specifically, a photothermal converter solution is prepared first. In this embodiment, polypyrrole is selected as the photothermal converter, which is prepared as follows: 0.228g of ammonium persulfate (APS) is weighed and dissolved in 20ml of deionized water, and 0.69ml of pyrrole (Py) is added thereto and stirred until dissolved. The amount of APS and Py added is added dropwise to 50ml and 1.2mol respectively, and the polymerization reaction is quenched with deionized water after 5min. After filtering and collecting polypyrrole (PPy), wash it three times and dry it, and then prepare PPy into a 20g / ml photothermal converter solution.

[0034] The sintered cinder block in step 1 is immersed in the photothermal conversion agent solution to adsorb the photothermal conversion agent for 2 hours. After the adsorption is completed, the PPy is solidified on the cinder block by drying to prepare a composite cinder.

[0035] When in use, the sewage to be treated is first placed in a water reservoir, and the treated composite coal slag is placed in the water reservoir. Based on the regulation of the porosity and density of the composite coal slag, the density of the composite coal slag is 0.8g / cm 3In this way, the composite coal slag can partially float on the water surface and partially be located under the water surface. Since the composite coal slag is adsorbed with a photothermal conversion agent and has a super strong light absorption capacity, under the irradiation of sunlight, the composite coal slag located on the water surface will absorb sunlight and convert it into heat, and the part located under the water surface is used to provide water supply. Since the heat is localized in a layer of water on the water surface, the heat can be used to evaporate water as much as possible without conducting it to the water body to cause additional energy loss. The evaporated water is recycled and reused to make pure water.

[0036] Example 2

[0037] The difference between this embodiment and embodiment 1 is that the sintering temperature in step 1 is 300°C.

[0038] Example 3

[0039] The difference between this embodiment and embodiment 1 is that the sintering temperature in step 1 is 400°C.

[0040] Example 4

[0041] The difference between this embodiment and embodiment 1 is that the sintering time in step 1 is 2 hours.

[0042] Example 5

[0043] The difference between this comparative example and Example 1 is that the photothermal conversion agent in step 2 is carbon black.

[0044] Example 6

[0045] The difference between this embodiment and embodiment 1 is that the adsorption amount of PPy in the composite coal slag is 2%.

[0046] Example 7

[0047] The difference between this embodiment and embodiment 1 is that the adsorption amount of PPy in the composite coal slag is 5%.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that the sintering temperature in step 1 is 200°C.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that the sintering temperature in step 1 is 500°C.

[0052] Comparative Example 3

[0053] The difference between this comparative example and Example 1 is that the sintering time in step 1 is 1 h.

[0054] Comparative Example 4

[0055] The difference between this comparative example and Example 1 is that the sintering time in step 1 is 3 hours.

[0056] Comparative Example 5

[0057] The difference between this comparative example and Example 1 is that the photothermal conversion agent in step 2 is a graphene suspension.

[0058] Comparative Example 6

[0059] The difference between this comparative example and Example 1 is that the adsorption amount of PPy in the composite coal slag is 1%.

[0060] Comparative Example 7

[0061] The difference between this comparative example and Example 1 is that the adsorption amount of PPy in the composite coal slag is 6%.

[0062] The density and porosity of the composite coal slag detector prepared in the above embodiments and comparative examples were tested for its photothermal conversion efficiency and water evaporation rate in sewage treatment. The experimental results are shown in Table 1 below.

[0063] Table 1: Example & Comparative Example Experimental Data Table

[0064]

[0065]

[0066] Experimental results analysis:

[0067] From the above results, it can be seen that the composite coal slag for sewage treatment provided by the present invention has suitable density, porosity and photothermal conversion agent adsorption capacity, and can ensure that the photothermal conversion efficiency reaches more than 90% during the sewage treatment process. And due to the suitable density and porosity, the composite coal slag has strong water absorption and water supply efficiency, and its water evaporation rate is improved.

[0068] Comparative Examples 1 and 2 changed the sintering temperature of the coal slag. When the sintering temperature is too low, the gas volatilization is less due to the incomplete sintering of the coal slag, resulting in a lower porosity of the composite coal slag, and the water supply cannot be guaranteed in sewage treatment, so the water evaporation rate is slow. When the sintering temperature is too high, the pore size of the composite coal slag increases, the capillary force weakens, and the water absorption and water supply capacity decreases.

[0069] Comparative Examples 3 and 4 changed the sintering time. If the sintering time is too short, the coal slag is not sintered completely, resulting in less gas volatilization, resulting in a lower porosity of the composite coal slag, and the water supply cannot be guaranteed in sewage treatment, so the water evaporation rate is slow. If the sintering time is too long, the pore size of the composite coal slag will increase, the sample structure will be loose, the capillary force will be weakened, and the water absorption and water supply capacity will be reduced.

[0070] Comparative Examples 6 and 7 change the adsorption amount of the photothermal conversion agent. When the photothermal conversion agent is less adsorbed, the light absorption capacity of the composite coal slag will decrease, thereby causing the sewage treatment efficiency of the composite coal slag to decrease. When the photothermal conversion agent is more adsorbed, the photothermal conversion agent will block the pores of the composite coal slag block, and the photothermal conversion effect will not increase proportionally but will decrease instead.

[0071] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the embodiments, it does not contain only one technical solution. This narrative of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing composite coal slag for sewage treatment, characterized in that: The following steps are involved: Step 1: collect and compress the burned coal slag solid waste into coal slag blocks, wherein the sintering temperature is 300-400° C. and the sintering time is 2-3 hours; Step 2: Immerse the coal slag block in a photothermal conversion agent solution, and dry and solidify it into a composite coal slag after adsorption. The concentration of the photothermal conversion agent solution is 20 to 30 g / ml. The photothermal conversion agent includes any one of polypyrrole, carbon black or graphite. The adsorption amount of the photothermal conversion agent is 2% to 5% of the weight of the composite coal slag.

2. A composite coal slag for sewage treatment prepared by the method for preparing a composite coal slag for sewage treatment according to claim 1, characterized in that: The composite coal slag is adsorbed with a photothermal conversion agent; the porosity of the composite coal slag is 70-90%; the density is 0.7-0.9 g / cm 3 .

Citation Information

Patent Citations

  • Preparation method and application of photo-thermal conversion assembly

    CN117073240A

  • Solar water evaporation photothermal conversion material and preparation method and application thereof

    CN117487527A

  • System for treating sewage and sludge using high-temperature light and heat

    CN105366865A

  • Copper-containing carbon-based composite efficient photothermal conversion material and preparation method thereof

    CN113023812A